Interferência e nível de dano econômico de milho voluntário em feijão - Aguiar, Adalin Cezar Moraes de (2018)
Among the factors that affect the bean culture, the interference imposed by the weeds stands out. In a second cropping system, bean became an option in the succession system after maize in southern Brazil. From this, corn seeds that remain in the post-harvest field can germinate during bean cultivation, and maize can become a problematic voluntary weed under these conditions. The objective of this study was to evaluate the relative competitiveness, damage to growth, development, morphology, physiology, grain yield and level of economic damage of the density interference and emergence time of volunteer corn in relation to beans. The research was developed in the period between 2015 and 2017, in a greenhouse, laboratory and field, where four studies were presented in the form of articles. The studies referring to articles I, II and III were conducted in a greenhouse and laboratory, while Article IV was conducted in the field. In article I the relative competitiveness of two bean cultivars in coexistence with volunteer corn was evaluated, which emerged at different times and proportions of plants in the association. In article II, the effect of the emergence interference of volunteer corn on growth parameters, photosynthetic pigments and chlorophyll fluorescence of bean cultivars in competition for light and soil + light resources was studied. The article III approached study on the interference of the emergence season of volunteer corn in competition with bean by the light and soil + light resources, in the growth and stomata of two bean cultivars. Article IV is related to the effect of the emergence season and volunteer corn density on grain yield loss and the level of economic damage in the beans. When volunteer corn emerges earlier, interference to beans is greater than simultaneous emergence. There is a significant correlation between bean plant growth variables and chlorophyll fluorescence, which makes it an important analysis tool used to quantify the stress caused by weeds. The effects of competition for soil + light resources are greater when compared to competition by light only, where the stomatal density of the beans increases when in competition with the volunteer corn only when the corn emerges in advance competing for both light and soil resources . Bean yield losses increase with the increase in volunteer corn density. The germination of the volunteer plant with the crop caused a greater reduction of the values of economic damage level, compared to the late emergence. The level of economic damage of volunteer maize independent of the simulation performed did not exceed 14,553 plants ha-1, and 902 plants ha-1 can reach the minimum population of control need. In this sense, the importance of bean sowing in infestation-free soil with volunteer corn plants can be highlighted, where values indicate the need to manage this species even at low densities.